A promising antitumor method: Targeting CSC with immune cells modified with CAR - Huang, Binjie; Miao, Lele; Liu, Jie; Zhang, Jiaxing; Li, Yumin (Frontiers in Immunology, 2022)
Tumors still pose a great threat to human health, as a subgroup of tumor cells, cancer stem cell(CSC) contributes to the genesis, development, metastasis and recurrence of tumor because of its enhanced proliferation and multi-directional differentiation, thus it`s a key step to eliminate CSC in tumor treatment. Researchers have proposed many different methods to inhibit or eliminate CSC, including monoclonal antibody targeting special surface molecule of CSC, signal pathway inhibitors, energy metabolic enzyme inhibitors, inducing differentiation therapy and immunotherapy, of which, immune-cells engineered with chemeric antigen receptor(CAR) showed favourable prospect, however, there are few comprehensive reviews in this area. In this review, we summarize the recent CSC targets used in CSC elimination, different immune effector cells(T cell, NK cell and macrophage) which are engineered with CAR used in CSC therapy. Finally, we list the main challenges and options in targeting CSC with CAR-based immunotherapy. The design which can target two tumor antigens(one CSC antigen and one mature common tumor antigen) should be more reasonable and effective; meanwhile, we highlight the potential of CAR-NK in tumor treatment.